Pengaruh Kapabilitas Inovasi, Modal Usaha, Diversifikasi Produk dan Pemahaman Akuntansi terhadap Keberlanjutan Bisnis UMKM Bidang Kuliner di Kota Semarang - Yulia Intan Pratiwi; Taufiq Andre Setiyono (Jurnal Inovasi Akuntansi (JIA), 2024)
This study aims to analyze the influence of innovation capability, venture capital, product diversification and accounting understanding on the sustainability of MSME businesses in Semarang City. The population of this study is MSME actors in the culinary field in Semarang City. The sample in this study was obtained using the Slovin formula, namely 331 MSMEs. This study is a quantitative study and was analyzed using the SPSS version 25 analysis tool. The results of the study indicate that innovation capability does not affect business sustainability. Venture capital has a significant positive effect on business sustainability. Product diversification has a significant positive effect on business sustainability. Accounting understanding has a significant positive effect on business sustainability.